What Excites Private Investors in The Game Development Industry? - Marcin OCIESZAK (Communications of International Proceedings, 2023)
This is a positioning paper trying to find possible research gaps in value creation among game development companies. This is a crucial problem considering the lack of information resulting from a very long delay in the publication of financial reports about the game's release date. The internet forums analysis identified what interests investors of companies apart from financial data. The study presents a list of potential determinants of stock price changes, like the scale of the community hub, a wish list on Steam, and the number of Twitch viewers, which can be used for further research.
Keywords: video games; market sentiment; value creation